OPTIMIZATION OF CONCENTRATION AND DURATION OF SEED NUTRIPRIMING WITH IRON SULPHATE FOR SEED QUALITY ENHANCEMENT IN BLACKGRAM - B. SAI SUDHA*, K .BAYYAPU REDDY, K. RADHIKA and V. SAIDA NAIK, (The Journal of Research ANGRAU, 2021)
The investigation was carried out to optimize the concentration and duration of nutriprimingwithiron sulphate for seed quality enhancement in blackgram variety, Tulasi. The experiment wasconducted during 2019-20 using Factorial Completely Randomized Design(FCRD) and replicatedfour times. Seeds were subjected to nutripriming with various concentrations (0, 0.01%, 0.05%, 0.1%and 0.5%) of iron sulphate for different durations (0, 2, 4, 6 and 8 h). Primed as well as unprimedseed of blackgram were tested for germination and seedling growth using between paper method. Itis evidentthat nutripriming with iron sulphatewas effective in improving the seed quality of Tulasi.Amongall the concentrations, 0.1% iron sulphate was found effective in recording highest germination (%),seedling length (cm) and seedling vigour index. Irrespective of concentration, priming for 6h showedmaximum improvement for seed quality parameters. Nutripriming with 0.05% iron sulphate for 6 hresulted in better enhancement of germination and seedling quality parameters in blackgram.